2000
DOI: 10.1074/jbc.275.17.12521
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Uncoupling Mechanism of Sarcoplasmic Reticulum ATPase Using the Phosphorylating Substrate UTP

Abstract: Ca2؉ transport and UTP hydrolysis catalyzed by sarcoplasmic reticulum Ca 2؉ -ATPase from skeletal muscle was studied. A passive Ca 2؉ load inside microsomal vesicles clearly decreased the net uptake rate and the final accumulation of Ca 2؉ but not the UTP hydrolysis rate, causing energy uncoupling. In the absence of passive leak, the Ca 2؉ /P i coupling ratio was 0.7-0.8. UTP hydrolysis did not maintain a rapid component of Ca 2؉ exchange between the cytoplasmic and lumenal compartments as occurs with ATP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Our finding of a nucleotide specific conformation of the nucleotide-ATPase complexes is supported by previous reports, in which different effects of different nucleotides were found on fluorescence properties (17,18,53), partial reaction rates (54 -57), protection against proteolysis (21), effects of aromatic compounds (58), nucleotide binding properties of mutants (25), and uncoupling (59).…”
Section: Discussionsupporting
confidence: 79%
“…Our finding of a nucleotide specific conformation of the nucleotide-ATPase complexes is supported by previous reports, in which different effects of different nucleotides were found on fluorescence properties (17,18,53), partial reaction rates (54 -57), protection against proteolysis (21), effects of aromatic compounds (58), nucleotide binding properties of mutants (25), and uncoupling (59).…”
Section: Discussionsupporting
confidence: 79%
“…An increase in internal free Ca 2ϩ produced complete uncoupling and slightly decreased the sensitivity to vanadate. Uncoupling through E 1 forms induced by lumenal Ca 2ϩ has already been characterized when the phosphorylating substrate is UTP (39).…”
Section: Ca 2ϩ -Atpase Reaction Cycle and P-nitrophenyl Phosphatementioning
confidence: 99%
“…It has been reported that SR Ca 2ϩ -ATPase is phosphorylated by and/or hydrolyzes ATP (40), UTP (39), or even the nonnucleotide substrate furylacryloylphosphate (41) in a Ca 2ϩ -free medium. In the case of pNPP, the rate of phosphorylation, which is much lower than that by ATP (25), does not allow the accumulation of phosphorylated intermediate during the enzyme turnover.…”
Section: Ca 2ϩ -Atpase Reaction Cycle and P-nitrophenyl Phosphatementioning
confidence: 99%
“…Data obtained in different laboratories indicate that the conversion of the phosphate compound from high to low energy is promoted by a change of water activity at the catalytic site of the enzyme, and this decrease can be explained by the solvation energy theory (33)(34)(35)(36)(37)(38)(39). forming an acyl phosphate residue of high energy (Table II), and translocation of Ca 2ϩ across the membrane occurs simultaneously with the conversion of the acyl phosphate from high into low energy (6,(13)(14)(15)(31)(32)(33). In leaky vesicles (no gradient) practically all the ATPase activity measured is coupled with the translocation of Ca 2ϩ across the membrane.…”
Section: Energy Of Hydrolysis Of Phosphate Compounds During Catalysismentioning
confidence: 99%
“…In this case, a part of the chemical energy derived from ATP cleavage is used for Ca 2ϩ transport, and a part is converted into heat. The second route is a shortcut of the transport cycle where the cleavage of ATP is completed in a step that precedes the translocation of Ca 2ϩ through the membrane, and all the energy derived from ATP hydrolysis is converted into heat (4,5,8,10,(13)(14)(15). Thus, during the course of the reaction, the amount of heat released varies depending on how much ATP is cleaved in each of these two routes.…”
mentioning
confidence: 99%